As exigências do discipulado cristão segundo Lc 9:23-27: uma análise bíblico-teológica das máximas de Jesus - Jacobini, Hiran E. C. (2021)
Jesus’ invitation to discipleship in Luke 9:23-27 is, without a doubt, primarily a call to surrender. The emphasis is on “deny themselves”, because all of those who accept the call need to know that they will have to leave certain things in the past, and only then start something new. And it is not just about following a new road, being walked by someone else, but letting be led by Him. However, Jesus walks through calvary. For this reason, He says that whoever chooses to follow him shall carry his cross: an act that reflects the radical nature of surrender and the kind of mindset need for the discipleship experience. Also, Jesus uses five maxims to express other issues that imply losses and gains, shame and promises. This dissertation proposes to analyze this speech, aiming to identify the meanings and implications of discipleship, considering discipleship is still the core of the Christian faith experience. This study follows a multidisciplinary approach, based on bibliographic analyzes and textual revision related to the discipleship experience in the context of Luke’s gospel. The exegetical theological method was applied from a synchronous approach within a pragmatic linguist perspective, following the fundamental steps of contemporary scientific exegesis